2018
DOI: 10.1016/j.pharmthera.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin activators and inhibitors: Promises, achievements, and challenges

Abstract: The NAD-dependent protein lysine deacylases of the Sirtuin family regulate various physiological functions, from energy metabolism to stress responses. The human Sirtuin isoforms, SIRT1-7, are considered attractive therapeutic targets for aging-related diseases, such as type 2 diabetes, inflammatory diseases and neurodegenerative disorders. We review the status of Sirtuin-targeted drug discovery and development. Potent and selective pharmacological Sirt1 activators and inhibitors are available, and initial cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
299
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(303 citation statements)
references
References 169 publications
(307 reference statements)
2
299
0
2
Order By: Relevance
“…Inspired by this study, we planned to carry out docking simulations by GOLD program (Jones et al, 1997). It has been reported that the indole EX-527 (6chloro-2,3,4,9-tetrahydro-1H-carbazole-1-carboxamide) proved to be a nanomolar SIRT1 inhibitor (Dai, Sinclair, Ellis, & Steegborn, 2018), whose hypothesized mechanism of inhibition has been reported (Zhao et al, 2013). To compare experimental and predicted binding modes, thus validating the docking procedure, in the first step of our in silico study, docking calculations were carried out by using EX-527 analogue by hydrophobic residues and maintains a fixed orientation through the π/π stacking between Phe273 and indole ring as reported by Zhao and coworkers (Zhao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by this study, we planned to carry out docking simulations by GOLD program (Jones et al, 1997). It has been reported that the indole EX-527 (6chloro-2,3,4,9-tetrahydro-1H-carbazole-1-carboxamide) proved to be a nanomolar SIRT1 inhibitor (Dai, Sinclair, Ellis, & Steegborn, 2018), whose hypothesized mechanism of inhibition has been reported (Zhao et al, 2013). To compare experimental and predicted binding modes, thus validating the docking procedure, in the first step of our in silico study, docking calculations were carried out by using EX-527 analogue by hydrophobic residues and maintains a fixed orientation through the π/π stacking between Phe273 and indole ring as reported by Zhao and coworkers (Zhao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…NAMPT is the ratelimiting enzyme in this pathway, and regulates sirtuin activity by modulating NAD + levels (Revollo et al, 2004). This entire pathway is related to aging processes (Dai et al, 2018), which were acquired by bilaterian animals along with tissue differentiation and cell cycle control mechanisms to evade cancer (Petralia et al, 2014). Indeed, these are the very types of biology with which PGRMC1 function is here implicated: suggesting that PGRMC1 phosphorylation could be involved in the mechanism(s) of animal aging.…”
Section: Discussionmentioning
confidence: 99%
“…A small trial conducted on the sirtuin‐1 activator SRT2104 suggested that the compound may improve measures of arterial stiffness in healthy smokers and diabetic patients . Clinical trials are being performed to assess the effects of drugs targeting sirtuin activities in humans …”
Section: Effects Of Plant and Fungal Compounds On Healthspanmentioning
confidence: 99%
“…327 Clinical trials are being performed to assess the effects of drugs targeting sirtuin activities in humans. 328 The NAD + precursor nicotinamide mononucleotide (NMN; 36) reduced diabetes in aging mice. 329 Another study show that NMN increases physical endurance in old mice by activating SIRT1 in endothelial cells.…”
Section: Effects Of Plant and Fungal Compounds On Healthspanmentioning
confidence: 99%